Key Dimensions of the Enterprise Architecture Value Drivers: Time Frame and Quantification - Rodrigues, Luis Silva (2016)
One of biggest issues that the managers of the Enterprise Architecture projects are facing is to justify the investments made in its construction and maintenance. Assessing the value of Enterprise Architectures is an increasingly important issue, however, it is not an easy task. Firstly, it is widely accepted that is very difficult for the organizations to identify the key value drivers. In addition, there are two dimensions of the value drivers that strongly influence the assessment of the Enterprise Architectures value: the time needed to realize the value drivers (time frame dimension) and the quantification of the value driver impact in the organization (quantification dimension). In this short paper is presented an initial discussion about the importance of these two dimensions in the assessment of Enterprise Architecture value.